APLIKASI “BERLIN COLLECTION” BERBASIS ANDROID - Prillasari, Ade; Khristianto, Teguh (Information Technology and Telematics, 2018)
Abstract - Shop Berlin Collection is a store that sells various kinds of clothing gamis fashion model with a modern and fashionable. The purpose of this research is to design the application of dressing gamis based on android. The method used to build system development is the prototype method. While the software (Software) used is Android Studio and for databases using MySQL. The results of the research on the Berlin Collection Shop can be concluded that with the construction of the application of fashion-based gamis dress on the Berlin Collection Store can facilitate customers in conducting transactions or the process of ordering goods, custom orders and get information about the Berlin Collection Shop.